Perbandingan Karakteristik Mortar Geopolimer Berbahan Dasar Fly Ash Nagan Raya Terhadap Mortar Konvensional Dengan FAS 0,5 - Aiyub Aiyub (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Alumina (Al) and silica (Si) compounds in Nagan Raya fly ash (FANR) greatly affect the characteristics of geopolymer mortar so that it can be compared to conventional mortar using OPC Semen Padang (OPCSP) with FAS 0.5. This study aims to obtain the optimum composition of geopolymer mortar using Nagan Raya fly ash, so that it can be compared to conventional mortar using OPC with FAS 0.5. This test is carried out using the parameters of workability, setting time and compressive strength in conventional mortar. Alkaline solution was prepared using 10M NaOH solution, the ratio of alkaline solution to FANR was 1.0 and 1.1, respectively, with the ratio of Na2SiO3 to NaOH 2, respectively; 2.5; 3; and 3.5. The results show that the optimum workability of geopolymer mortar is 19.15 cm where this workability is close to the workability of conventional mortar of 19.2 cm, the optimum setting time of geopolymer mortar is 165 minutes where this setting time is close to the conventional mortar setting time of 191 minutes and the optimum compressive strength of mortar. geopolymer obtained at 28.86 MPa where the compressive strength is close to the compressive strength of conventional mortar of 34.38 MPa. So that geopolymer mortar based on FANR is still feasible to use and has a characteristic approach to conventional mortar made from OPCSP with FAS 0.5.